Euroscepticism : images of Europe among mass publics and political elites - Fuchs, Dieter; Magni-Berton, Raul; Roger, Antoine (Barbara Budrich Publishers, 2009)
Of the Results (Raul Magni-Berton, Dieter Fuchs, Antoine Roger)Biographical Notes